Underwater Visual Records of Marine Megafauna Around Offshore Anthropogenic Structures - Todd, Victoria L. G.; Lazar, Laura; Williamson, Laura D.; Peters, Ingrid T.; Hoover, Aimee L.; Cox, Sophie E.; Todd, Ian. B.; Macreadie, Peter I.; McLean, Dianne L. (Frontiers in Marine Science, 2020)
In oceans and seas worldwide, an increasing number of end-of-life anthropogenic offshore structures (e.g. platforms, pipelines, manifolds, windfarms, etc.) are facing full or partial removal. As part of the decommissioning process, studies on potential importance of subsea infrastructure to marine megafauna (defined as: cetaceans, pinnipeds, sirenians, large fish – such as sharks, rays, billfishes, and tuna, as well as marine reptiles, and seabirds) are lacking. Dedicated scientific Remotely Operated Vehicle (ROV) surveys around offshore installations are rare, but there is a wealth of archived industrial data and noteworthy species sightings posted publicly on various social media platforms. This study used routine, incidentally-collected ROV (n = 73) and commercial diver (n = 9) video recordings spanning 1998–2019 globally. Data were gathered directly from industrial partners (n = 36) and the public domain (YouTube; n = 46) to provide an account of marine megafauna presence and potential feeding behaviour in the near visible vicinity of subsea anthropogenic structures. A total of 79 video clips and 3 still images of marine megafauna near offshore structures were examined, resulting in 67 individual sightings and 16 sub-sightings (in which an individual was recorded within the same day). At least 178 individuals were identified to a minimum of 17 species of marine megafauna, amounting to a total (combined) sighting duration of 01:09:35 (hh:mm:ss). Results demonstrated proximate presence of marine megafauna (many of which are threatened species) to anthropogenic structures, with most animals displaying foraging or interaction behaviours with the structures. Observations included the deepest (2,779 m) confirmed record of a sleeper shark (Somniosus spp.) and the first confirmed visual evidence of seals following pipelines. These ROV observations demonstrate a latent source of easily-accessible information that can expand understanding of marine megafauna interactions with offshore anthropogenic infrastructure. Consequently, other workers in this field should be encouraged to re-analyse archived datasets, commence further collaborative research projects with industrial partners, and/or expand Internet search terms to additional species assemblages, in a bid to quantitatively elucidate relationships between offshore infrastructure and marine species.